Synthesis and characterization of chitosan sheet modified by varied weight ratio of anatase (TiO2) nano mixture with Cr(VI) adsorbing - Zaid H. Mahmoud; Achraf Hamrouni; Asmaa B. Kareem; Mohammed Ahmed Mostafa; Zahara Jalil alhakim; Abdulwahhab H. Majeed (Kuwait Journal of Science)
TiO2 and varied weight TiO2 incorporated Chitosan (CS–TiO2) were successfully prepared via photolysis method utilizing manual UV irradiation system with a maximum intensity wavelength 256 ​nm and 125 ​W power source to remove Cr(VI) from aqueous solution. The structure and morphology properties were characterized by utilizing XRD, Raman spectrum, BET, TEM and FESEM. The mechanism of Cr(VI) were investigated by XPS. The best conditions for removing Cr(VI) from the aqueous solution were investigated by examining the effects of adsorption parameters, including pH, contact time, catalyst dosage, dye concentration, and temperature. The Freundlich and Isotherm of Langmuir models were used to characterize the equilibrium data of Cr(VI) removal by CS-TiO2, and the pseudo-first order, pseudo-second order, and Elovich models were used to study the adsorption kinetics. By employing CS-TiO2 nano mixture adsorbents, the thermodynamics parameters showed an endothermic reaction and the spontaneous nature. The maximal adsorption capacity (qmax) for Cr(VI) sorption was 60 ​mg ​g−1. The reusability of the chitosan and TiO2 nano mixture combination was tested for a fifth cycle, and the results demonstrated that it was equivalent to other adsorbents. Thus, this present study recommends the choice of 30 ​mg of absorbent (5wt.% TiO2:CS) for removing Cr(VI) from aqueous solution.